2019
DOI: 10.7710/2162-3309.2268
|View full text |Cite
|
Sign up to set email alerts
|

Data Management Practices in Academic Library Learning Analytics: A Critical Review

Abstract: INTRODUCTION Data handling in library learning analytics plays a pivotal role in protecting patron privacy, yet the landscape of data management by librarians is poorly understood. METHODS This critical review examines data-handling practices from 54 learning analytics studies in academic libraries and compares them against the NISO Consensus Principles on User's Digital Privacy in Library, Publisher, and Software-Provider Systems and data management best practices. RESULTS A number of the published research p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Briney found that only about 10 percent of published library LA studies mention data security practices. 133 These findings are echoed in Perry et al, where just over half of the survey respondents claim that they have security protections (physical and/ or digital) on LA data, and only a third secure data during transit. Additionally, fewer than half of respondents had a retention schedule for LA data, and a full 20 percent planned to hold onto these data "indefinitely."…”
Section: Practical Library Ethical Privacy Issuesmentioning
confidence: 96%
See 1 more Smart Citation
“…Briney found that only about 10 percent of published library LA studies mention data security practices. 133 These findings are echoed in Perry et al, where just over half of the survey respondents claim that they have security protections (physical and/ or digital) on LA data, and only a third secure data during transit. Additionally, fewer than half of respondents had a retention schedule for LA data, and a full 20 percent planned to hold onto these data "indefinitely."…”
Section: Practical Library Ethical Privacy Issuesmentioning
confidence: 96%
“…116 In a recent piece, Jones, Rubel, and LeClere argue institutions are beholden to their students as "information fiduciaries," that they have a moral obligation to use LA to benefit students and respect the trust students place in their university. 117 Given these known ethical problems and quandaries related to LA, Asher et al argue that librarians must update their sense of threats to user privacy by taking into account algorith-mic bias, reidentification, widespread data trading and hoarding, and surveillance creep. 118 Briney homes in on research ethics and LA projects, noting that, even though institutional review boards (IRB) are responsible for identifying ethical issues, many miss violations of library privacy ethics.…”
Section: Library Learning Analytics Ethics and Privacy Issuesmentioning
confidence: 99%
“…22 In a recently published critical review of the literature about data-handling practices from 54 learning analytics studies in academic libraries, Briney found many examples of inadequate data management practices, including "extended data retention, a broad scope of data collection, insufficient anonymization, lack of informed consent, and sharing of patron-identified data." 23 Briney further recommended that researchers become more transparent in documenting and sharing how they have worked through legal requirements, policies, and practices related to data handling in learning analytics' projects. In this article, the authors describe how they incorporated the NISO Privacy Principles, the Code of Practice for Learning Analytics, and Briney's recommendations as they designed the present study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Datasets created for learning analytics activities are particularly vulnerable to re-identification, even after de-identification and anonymization techniques have been utilized. (Asher 2017;Briney forthcoming;Metcalf & Crawford 2016). This vulnerability potentially exposes these data's constituent individuals and populations to unintended disclosures and insufficiently considered reuse or misuse by unexpected actors, including commercial, governmental, or law enforcement interests, such as investigatory requests and subpoenas.…”
Section: Ethics and Library Learning Analyticsmentioning
confidence: 99%